Malaria exacerbates inflammation‐associated elevation in ferritin and soluble transferrin receptor with only modest effects on iron deficiency and iron deficiency anaemia among rural Zambian children. Issue 1 (24th November 2017) - Barffour, Maxwell A.; Schulze, Kerry J.; Coles, Christian L.; Chileshe, Justin; Kalungwana, Ng'andwe; Siamusantu, Ward; Arguello, Margia; Moss, William J.; West, Keith P.; Palmer, Amanda C.
Abstract: Objective: In 4‐ to 8‐year‐old Zambian children ( n = 744), we evaluated the effects of adjusting for inflammation ( α 1‐acid glycoprotein >1 g/l), with or without additional adjustment for malaria, on prevalence estimates of iron deficiency (ID) and iron deficiency anaemia (IDA) during low malaria (LowM) and high malaria (HighM) transmission seasons. Methods: To estimate adjustment factors, children were classified as: (i) reference (malaria negative without inflammation), (ii) inflammation without malaria (I), (iii) malaria without inflammation (M) and (iv) inflammation with malaria (IM). We estimated the unadjusted ID or IDA prevalence, and then adjusted for inflammation alone (IDI or IDAI ) or inflammation and malaria (IDIM or IDAIM ). Results: Mean ferritin was 38 (reference), 45 (I), 43 (M) and 54 μg/l (IM) in LowM, increasing to 44, 56, 96 and 167 μg/l, respectively, in HighM. Corresponding mean sTfR was 6.4, 6.9, 7.9 and 8.4 mg/l in LowM, increasing to 8.2, 9.2. 8.7 and 9.7 mg/l in HighM. Ferritin‐based ID, IDI and IDIM were 7.8%, 8.7% or 9.1%, respectively, in LowM and 4.6%, 10.0% or 11.7%, respectively, in HighM. Corresponding soluble transferrin receptor (sTfR)‐based estimates were 27.0%, 24.1% and 19.1%, respectively, in LowM, increasing to 53.6%, 46.5% and 45.3%, respectively, in HighM. Additional adjustment for malaria resulted in a ~1‐ to 2‐percentage point change in IDA, depending on biomarker and season. Conclusions: In this population, malaria substantially increased ferritin and sTfR concentrations, with modest effects on ID and IDA prevalence estimates.